Positioning system based on inertial measurement unit and ultra-wideband impulse radio - Tang, Jiaqi (Nanyang Technological University, 2021)
In recent years, indoor positioning has become a popular topic. This project uses inertial measurement unit (IMU) and ultra-wideband impulse radio (UWB-IR) technology to realize an indoor ranging and positioning system. IMU and UWB positioning methods and principles are introduced. MATLAB is used in this project to verify the feasibility and accuracy of the positioning methods. The least square method is applied to find an approximate UWB positioning result. A 15-dimensional Error state Kalman filter (ESKF) is used as a data fusion algorithm to reduce the impact of NLOS and eliminate errors. When the orientation result calculated from the IMU data is used as a correction, the influence of NLOS can be greatly eliminated. At last, the results of several positioning methods are presented and compared, it is found that pure IMU positioning cannot achieve positioning due to accumulated errors, and pure UWB positioning have great errors because of NLOS. Only by fusing the UWB with the IMU sensor can a more accurate trajectory of the object be obtained.